Upaya Meningkatkan Pengetahuan Gizi dan Kebiasaan Makan Sehat serta Meningkatkan Kebugaran Jasmani Siswa Sekolah Dasar melalui Program Edukasi PJOK - siddik, Fajar; Parista, Icha; Harahap, Wafa Syakura; Azzahra, Mayla Fitri; Aprilia, Indah (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The issue of nutrition and physical fitness in primary school students in Indonesia is still a concern. Lack of nutritional knowledge and healthy eating habits, as well as low physical activity are the main factors. This study aims to examine the PJOK education program in improving nutritional knowledge, healthy eating habits, and physical fitness of elementary school students. The research method used is the literature study method, to collect data from various trusted sources, such as scientific journals, scientific articles, and research reports. Data were analyzed qualitatively to identify effective PJOK education programs and their impact on nutrition knowledge, healthy eating habits, and physical fitness of elementary school students. The results showed that a physical education program integrated with nutrition and physical activity learning materials can significantly improve nutrition knowledge, healthy eating habits, and physical fitness of primary school students. This program needs to be implemented in a sustainable manner and involve various related parties, such as teachers, parents, and the school community.